THE EMEMERGENC OF THE SCHOOL OF COMPOSITION IN UZBEKISTAN - Farangis Ikromova Yigitali qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article describes the formation of composer schools in Uzbekistan by talented composer and teacher Boris Borisovich Nadejdin who has great contribution for developing composing school and their thoughts and opinions in this sphere.